2016
DOI: 10.5511/plantbiotechnology.16.0503a
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of <i>Nicotiana benthamiana</i> SEC14 phospholipid transfer protein reduced jasmonic acid dependent defense against <i>Pseudomonas syringae</i>

Abstract: We previously identified SEC14, phospholipid transfer protein superfamily gene, in Nicotiana benthamiana (NbSEC14) that was closely related to phospholipid signaling as well as jasmonic acid-dependent defense responses during plant immune responses against Ralstonia solanacearum. To examine effect of NbSEC14-silencing on basal plant defenses, we used two other bacterial pathogens with different virulent strategies, Pseudomonas syringae pv. tabaci and pv. mellea. NbSEC14-silenced plants showed accelerated growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We have previously identified the SEC14 gene in N. benthamiana . Suppression of PLC and PLD activities, and production of diacylglycerol (DAG) and PA were observed in NbSEC14- silenced plants, resulting in compromised disease resistance against phytopathogenic bacteria through the jasmonic acid (JA)-dependent pathway ( Kiba et al, 2012 , 2014 , 2016 ). Thus, phospholipid turnover may play an important role in the induction of immune responses in N. benthamiana .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified the SEC14 gene in N. benthamiana . Suppression of PLC and PLD activities, and production of diacylglycerol (DAG) and PA were observed in NbSEC14- silenced plants, resulting in compromised disease resistance against phytopathogenic bacteria through the jasmonic acid (JA)-dependent pathway ( Kiba et al, 2012 , 2014 , 2016 ). Thus, phospholipid turnover may play an important role in the induction of immune responses in N. benthamiana .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we identified the SEC14 gene, encoding a phospholipid transfer protein, in Nicotiana benthamiana (NbSEC14). The suppression of phospholipase C and D activities and a reduction in the PA content have been observed in NbSEC14-silenced plants, resulting in compromised resistance against phytopathogenic bacteria (Kiba et al 2012(Kiba et al , 2014(Kiba et al , 2016. We also reported that phosphoinositide-specific phospholipase C2 in N. benthamiana participates in basal disease resistance (Kiba et al 2020).…”
mentioning
confidence: 65%